2017
DOI: 10.1111/jfb.13329
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive strategy, spawning induction, spawning temperatures and early life history of captive sicklefin chub Macrhybopsis meeki

Abstract: Macrhybopsis reproduction and propagule traits were studied in the laboratory using two temperature regimes and three hormone treatments to determine which methods produced the most spawns. Only sicklefin chub Macrhybopsis meeki spawned successfully although sturgeon chub Macrhybopsis gelida released unfertilized eggs. All temperature and hormone treatments produced M. meeki spawns, but two treatments had similar success rates at 44 and 43%, consisting of a constant daily temperature with no hormone added, or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 72 publications
(168 reference statements)
2
32
1
Order By: Relevance
“…These population dynamics are consistent with other life history studies on Great Plains Macrhybopsis spp. (Albers & Wildhaber, 2017;Albers, Wildhaber, & Green, 2018;Perkin, Shattuck, Gerken, & Bonner, 2013;, except that no age 0 individuals were detected in our study. By 2012, only a single age 2 peppered FIGURE 2 Temporal patterns in gonadosomatic index (GSI) for females (top row) and males (middle row) as well as length-frequency plots for the sizes (total length, mm) of individuals captured (bottom row) for six fish species collected during 11 samples in the summer of 2011 (see Table 1 for all dates).…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…These population dynamics are consistent with other life history studies on Great Plains Macrhybopsis spp. (Albers & Wildhaber, 2017;Albers, Wildhaber, & Green, 2018;Perkin, Shattuck, Gerken, & Bonner, 2013;, except that no age 0 individuals were detected in our study. By 2012, only a single age 2 peppered FIGURE 2 Temporal patterns in gonadosomatic index (GSI) for females (top row) and males (middle row) as well as length-frequency plots for the sizes (total length, mm) of individuals captured (bottom row) for six fish species collected during 11 samples in the summer of 2011 (see Table 1 for all dates).…”
Section: Discussioncontrasting
confidence: 71%
“…These population dynamics are consistent with other life history studies on Great Plains Macrhybopsis spp (Albers & Wildhaber, 2017;Albers, Wildhaber, & Green, 2018;Perkin, Shattuck, Gerken, & Bonner, 2013;,. Age 0 fishes appeared or increased in number during June 2011 approximately after peak GSI, including emerald shiner (June 28), sand shiner (June 14), red shiner (June 28), and bullhead minnow (June 14).…”
supporting
confidence: 91%
“… References: 1 Platania and Altenbach (); 2 Hoagstrom and Turner (); 3 Coleman (); 4 G. Wilde unpublished data; 5 Hoagstrom, Hayer, et al. (); 6 Albers and Wildhaber (); 7 Simon (); 8 Haworth and Bestgen (); 9 K. Bestgen unpublished data; 10 Flittner (); 11 Williams and Bonner (). …”
Section: Methodsmentioning
confidence: 99%
“…Standardized assessments of relative chub abundance have shown large fluctuations in annual catch with indications of declining stocks (Wildhaber, Gladish, & Arab, ; Wildhaber, Yang, & Arab, ). Only recently was it confirmed that the three benthic species of Macrhybopsis that inhabit the Missouri River (MR) are members of the pelagic broadcast spawning guild and pass through an egg and larval drifting phase (Albers & Wildhaber, ; Reeves & Galat, ). With increased knowledge comes concerns about effects of human‐created restrictions on distribution, population sustainability, and potential need for protection due to limited stocks (U.S Fish and Wildlife Service, USFWS, ; Dieterman & Galat, ; Ridenour, Meyer, Wrasse, Doyle, & Hill, ; Perkin & Gido, ) as well as these species’ role in recovery of the MR fish community (Gerrity et al, ).…”
Section: Introductionmentioning
confidence: 99%